ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN PADA RESTORAN BENTOMIE SAMASTA TELAGA KAHURIPANKABUPATEN BOGOR - Utomo, Styo Budi; Karlina, Siti (SINERGI : Jurnal Riset Ilmiah, 2025)
This research aims to find out and analyze how the leadership style is applied at the Bentomie Samasta Telaga Kahuripan Restaurant, Bogor Regency, as well as how this leadership style can influence improving the performance of Bentomie Samasta Telaga Kahuripan Restaurant employees, Bogor Regency. According to Miles and Huberman "there are 3 (three) activities in data analysis, namely data reduction, data presentation and drawing conclusions". Based on observations and interviews with five informants representing the Bentomie Samasta Telaga Kahuripan Restaurant, Bogor Regency, the leadership style applied by superiors has a real influence on employee performance, leaders tend to use a participative leadership style. In general, the leadership style applied has been able to improve employee performance, but still needs improvement in aspects of work discipline, communication, coordination and service consistency in order to be more competitive and professional. Based on the results of the research conducted, researchers suggest that leaders emphasize the importance of open and routine communication through short face-to-face briefings before or after working hours to equalize perceptions, provide simple training and routine motivation, so that employees have additional skills and enthusiasm at work